Scanning Electron Microscopy Analysis of Tea’s Embryo Axis Explant Cultured on Murashige and Skoog Medium Containing 2,4-Dichlorophenoxyacetic acid - Eskundari, Ratna Dewi; Taryono, Taryono; Indradewa, Didik; Purwestri, Yekti Asih (Universitas Gadjah Mada, 2024)
Camellia sinensis L. is an important crop in Indonesia as healthy beverage that contains several secondary metabolism compounds, such as polyphenols and catechins. Tissue culture including somatic embryogenesis and organogenesis has been used for propagating plant for various needs. In this present short-communication, scanning electron microscopic (SEM) analysis of tea was conducted and discussed. This study aimed to investigate surface ultrastructure of TRI2025 embryo axis tea clone cultured on Murashige and Skoog (MS) medium containing 2,4-Dichlorophenoxyacetic acid (2,4-D). The results revealed two different forms of explant’s development, i.e. somatic embryo and transitional form between somatic embryogenesis and organogenesis; or called by “Globular-like Structure” (GLS). Surface ultrastructure analysis of somatic embryo and GLS revealed respectively many stages of somatic embryo development i.e. globular, torpedo, and cotyledon stage, and leaf development form GLS regeneration.